Apparent Acquired Resistance by a Weevil to Its Parasitoid Is Influenced by Host Plant - Goldson, Stephen L.; Tomasetto, Federico (Frontiers in Plant Science, 2016)
Field parasitism rates of the Argentine stem weevil Listronotus bonariensis (Kuschel; Coleoptera: Curculionidae) by Microctonus hyperodae Loan (Hymenoptera: Braconidae) are known to vary according to different host Lolium species that also differ in ploidy. To further investigate this, a laboratory study was conducted to examine parasitism rates on tetraploid Italian Lolium multiflorum, diploid Lolium perenne and diploid hybrid L. perenne ×L. multiflorum; none of which were infected by Epichloë endophyte. At the same time, the opportunity was taken to compare the results of this study with observations made during extensive laboratory-based research and parasitoid-rearing in the 1990s using the same host plant species. This made it possible to determine whether there has been any change in weevil susceptibility to the parasitoid over a 20 year period when in the presence of the tetraploid Italian, diploid perennial and hybrid host grasses that were commonly in use in the 1990’s. The incidence of parasitism in cages, in the presence of these three grasses mirrored what has recently been observed in the field. When caged, weevil parasitism rates in the presence of a tetraploid Italian ryegrass host were significantly higher (75%) than rates that occurred in the presence of either the diploid perennial (46%) or the diploid hybrid (52%) grass, which were not significantly different from each other. This is very different to laboratory parasitism rates in the 1990s when in the presence of both of the latter grasses high rates of parasitism (c. 75%) were recorded. These high rates are typical of those still found in weevils in the presence of both field and caged tetraploid Italian grasses. In contrast, the abrupt decline in weevil parasitism rates points to the possibility of evolved resistance by the weevil to the parasitoid in the diploid and hybrid grasses, but not so in the tetraploid. The orientation of plants in the laboratory cages had no significant effect on parasitism rates under any treatment conditions suggesting that plant architecture may not be contributing to the underlying mechanism resulting in different rates of parasitism. The evolutionary implications of what appears to be plant-mediated resistance of L. bonariensis to parasitism by M. hyperodae are discussed.